2018
DOI: 10.1021/jacs.8b05459
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Properties of a Peptidic Catalyst: Insights from NMR Spectroscopic Studies

Abstract: Peptides have become valuable as catalysts for a variety of different reactions, but little is known about the conformational properties of peptidic catalysts. We investigated the conformation of the peptide H-dPro-Pro-Glu-NH, a highly reactive and stereoselective catalyst for conjugate addition reactions, and the corresponding enamine intermediate in solution by NMR spectroscopy and computational methods. The combination of nuclear Overhauser effects (NOEs), residual dipolar couplings (RDCs), J-couplings, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 158 publications
5
58
0
1
Order By: Relevance
“…C (32) 116 (15) 115 (16) 114 15-1 628 71 6C (33) 190(20) 150 (40) 60 2020 (30) 40 (18) 40 20C (34) 210 (30) 210 (30) 210 (30) 0 (6) 55 101 6C (35) 240 (30) 210 50190 4020 (40) 100 (30) 60 30C (36)…”
Section: ____________________________________________________________unclassified
“…C (32) 116 (15) 115 (16) 114 15-1 628 71 6C (33) 190(20) 150 (40) 60 2020 (30) 40 (18) 40 20C (34) 210 (30) 210 (30) 210 (30) 0 (6) 55 101 6C (35) 240 (30) 210 50190 4020 (40) 100 (30) 60 30C (36)…”
Section: ____________________________________________________________unclassified
“…Supporting information for this article is available on the WWW under https://doi.org/10.1002/hlca.201900052 Our research group has been using the unique structural and functional properties of proline and proline derivatives bearing substituents at C(γ) for applications in chemical biology, supramolecular chemistry, and asymmetric catalysis. [5,[12][13][14][15][16][17] Recently, we became interested in peptides containing methylaryl substituents at C(γ) for their value as selective binders of the bacterial second messenger c-di-GMP. [18] Specifically, peptides consisting of cationic residues and (2S,4R)-4-[(naphthalen-2-yl)methyl]proline exhibit excellent binding affinity and selectivity towards c-di-GMP.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Recently, we analyzed the conformation of the ground state catalyst H-DPro-Pro-Glu-NH 2 and the respective enamine intermediate. [21] [22] NMR Spectroscopic studies showed that the peptide adopts a single predominant conformation in its ground state. This structure is a type I β-turn, which is stabilized by three hydrogen bonds that are formed cooperatively between all functional groups -the secondary amine, the carboxylic acid, and the amide groups (Scheme 1,a).…”
Section: Introductionmentioning
confidence: 99%
“…This structure is a type I β-turn, which is stabilized by three hydrogen bonds that are formed cooperatively between all functional groups -the secondary amine, the carboxylic acid, and the amide groups (Scheme 1,a). [22] The conformation of the enamine intermediate is more flexible as revealed by NMR spectroscopic and computational studies. A β-turn is still the dominant structure but the interaction of the CO 2 H group with the N-terminal amine is broken up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation